2018
DOI: 10.3390/genes9050244
|View full text |Cite
|
Sign up to set email alerts
|

Chitinase mRNA Levels Determined by QPCR in Crab-Eating Monkey (Macaca fascicularis) Tissues: Species-Specific Expression of Acidic Mammalian Chitinase and Chitotriosidase

Abstract: Mice and humans express two active chitinases: acidic mammalian chitinase (AMCase) and chitotriosidase (CHIT1). Both chitinases are thought to play important roles in specific pathophysiological conditions. The crab-eating monkey (Macaca fascicularis) is one of the most frequently used nonhuman primate models in basic and applied biomedical research. Here, we performed gene expression analysis of two chitinases in normal crab-eating monkey tissues by way of quantitative real-time polymerase chain reaction (qPC… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 42 publications
0
6
0
Order By: Relevance
“…Acidic chitinase (Chia; also referred to acidic mammalian chitinase, “AMCase”; Boot et al 2001 , 2005 ) hydrolyzes the β-1, 4 glycoside bonds of chitin, a major structural polysaccharide in insects ( Bueter et al 2013 ; Wysokowski et al 2015 ; Van Dyken and Locksley 2018 ). Chia is expressed in the stomachs of insectivorous and omnivorous animals including bat ( Strobel et al 2013 ), mouse ( Ohno et al 2016 ), pangolin ( Ma et al 2018 ), crab-eating monkey ( Uehara et al 2018 , 2021 ), and common marmoset ( Tabata, Kashimura, et al 2019 ). In addition, omnivorous livestock animals, such as chicken and pig, express Chia at high levels in their stomachs and are able to degrade chitin and chitin-containing materials such as shrimp shells and mealworm larvae shells under normal gastrointestinal conditions ( Tabata, Kashimura, Wakita, Ohno, Sakaguchi, Sugahara, Imamura, et al 2017 ; Tabata, Kashimura, Wakita, Ohno, Sakaguchi, Sugahara, Kino, et al 2017 ; Tabata, Kashimura, Wakita, et al 2018 ; Tabata, Wakita, et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…Acidic chitinase (Chia; also referred to acidic mammalian chitinase, “AMCase”; Boot et al 2001 , 2005 ) hydrolyzes the β-1, 4 glycoside bonds of chitin, a major structural polysaccharide in insects ( Bueter et al 2013 ; Wysokowski et al 2015 ; Van Dyken and Locksley 2018 ). Chia is expressed in the stomachs of insectivorous and omnivorous animals including bat ( Strobel et al 2013 ), mouse ( Ohno et al 2016 ), pangolin ( Ma et al 2018 ), crab-eating monkey ( Uehara et al 2018 , 2021 ), and common marmoset ( Tabata, Kashimura, et al 2019 ). In addition, omnivorous livestock animals, such as chicken and pig, express Chia at high levels in their stomachs and are able to degrade chitin and chitin-containing materials such as shrimp shells and mealworm larvae shells under normal gastrointestinal conditions ( Tabata, Kashimura, Wakita, Ohno, Sakaguchi, Sugahara, Imamura, et al 2017 ; Tabata, Kashimura, Wakita, Ohno, Sakaguchi, Sugahara, Kino, et al 2017 ; Tabata, Kashimura, Wakita, et al 2018 ; Tabata, Wakita, et al 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…31 This may suggest that the highest enzymatic activity can be found in gastric mucosa. 20 AMCase is expressed by lung epithelial cells and macrophages. AMCase mRNA expression and the number of AMCase-positive cells are upregulated during Th2 inflammation.…”
Section: Acid Mammalian Chitinasementioning
confidence: 99%
“…Higher AMCase enzyme and mRNA levels were found in omnivores (eg, pigs, chickens, monkeys) than in herbivores (eg, bovines) and carnivores (eg, dogs). 19,20 The highest levels of chitinase expression were reported in the lungs, stomach, kidney, and liver. 19,20 It may be hypothesized that a higher exposure to chitin-containing organisms results in the overexpression of chitinase genes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…These primates feed on crabs and other chitin-containing organisms such as crustaceans and insects [41]. Previously, we performed a gene expression analysis and showed that the monkey expresses a high level of CHIA mRNA in the stomach [42]. Crab-eating monkey CHIA is 50 times more active than the human analogue [43].…”
Section: Introductionmentioning
confidence: 99%